Evaluation of the Factors Promoting Maternal Mortality in Wukari LGA - Egeonu US; Boyi RN; Boyi BI; Adeoti II (African Journal of Medicine, Surgery and Public Health Research, 2026)
Maternal mortality remains a major public health concern, particularly in non-urban African settings where socioeconomic, infrastructural, and cultural barriers continue to limit progress in reducing preventable maternal deaths. This study assessed the factors contributing to maternal mortality in Wukari Local Government Area, Taraba State. A mixed-methods approach was employed, involving structured questionnaires administered to 400 respondents selected through simple random sampling across the 10 wards of Wukari LGA. Interviews were also conducted with healthcare providers, traditional birth attendants, and community leaders. Quantitative data were analyzed using descriptive statistics, including frequencies and percentages, and inferential statistics through the chi-square test, while qualitative data were analyzed thematically. The findings indicate that socioeconomic factors, including low income, limited education, and distance to the nearest health facility, influenced maternal health outcomes. Cultural practices were also prevalent, particularly reliance on traditional birth attendants, reported by 319 respondents (82.4%), and home deliveries, reported by 161 respondents (41.6%). Hypothesis testing showed that socioeconomic factors, limited access to healthcare facilities, and cultural practices significantly influenced the prevalence of maternal mortality in Wukari LGA (p < 0.05). The study concludes that maternal mortality in Wukari LGA is driven by interconnected socioeconomic, infrastructural, and cultural factors. These findings contribute to maternal health research by highlighting the combined influence of household-level, health-system, and cultural determinants of maternal mortality. Practical implications include the need to upgrade health facilities, expand community education programs, subsidize maternal health services, and integrate traditional birth attendants into formal healthcare systems to reduce maternal mortality in Wukari LGA.